Interaction of self-healing epoxy coating and microencapsulated inhibitor for the corrosion protection of magnesium alloys - Nurul Amiratul, Johari (2023)
Metal corrosion is one of the loss factors for industrial sectors, for example, in transport, civil and marine engineering, and medical engineering. Painting or epoxy coating is one of the best methods to protect metal from corrosion. However, the coating is subject to external events such as micro-cracks that shorten the service life of the coating and allow the corrosion process to occur. Therefore, traditional coatings must be upgraded to self-healing coatings, combined with encapsulated healing agents or corrosion inhibitors to heal cracks and protect metal from corrosion. In this study, the epoxy coating was combined with microcapsules containing honey with different concentrations (0%, 10%, 20%, 30% and 40% v/v), Aloe vera (10% v/v) and linseed oil (50% v/v) with 800 rpm and 1100 rpm as stirring rate. This study aims to investigate the optimum value of honey concentration and stirring rate of microencapsulation in resisting the corrosion of Mg alloys and to evaluate the corrosion behavior of self-healing epoxy coated Mg alloys in a corrosive environment. These microcapsules were successfully produced through in-situ polymerization of polyurea formaldehyde (PUF) microcapsules and embedded into an epoxy coating. Microcapsules and epoxy coating morphology were evaluated by scanning electron microscopy with energy-dispersive X-ray analysis (SEM with EDX). The physio-chemical properties of the microcapsules were investigated using Fourier-transform infrared spectroscopy (FTIR) and UV-Vis spectroscopy. Electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) were used to evaluate the defensive performance of self-healing epoxy-coated Mg alloy samples. The images from the optical microscope revealed that the microcapsules range in diameter from 56 μm to 83 μm. The size decreases as the rate of stirring rate during synthesis increases. The surface of the microcapsules with a stirring rate of 800 rpm looks rougher than the microcapsules produced by a stirring rate of 1100 rpm. FTIR spectra revealed that linseed oil and honey were successfully encapsulated in the PUF shell. The surface morphology of the self-healing coating shows a smooth surface and the presence of microcapsules in the cross-sectional area of the layer. Approximation with a thin film applicator results in 100 μm coating thickness. Honey was also identified as a component of the healing area due to the detection of potassium, sodium, and calcium using EDX elemental analysis, which determines the reaction of honey to its environment to form the protective layer. PDP analysis determined that the self-healing coating composed of 30% (v/v) honey, stirred at 800 rpm, offered the highest corrosion protection on the Mg alloy, with a lower corrosion current density, Icorr (0.032 μA/cm2) than the exposed magnesium sheet (1050 μA/cm2), showing transient passivation behaviour. The EIS Nyquist plot exhibits a curve that resembles a half-semicircle for each sample, displaying the active charge transfer between the coating and the sodium chloride (NaCl) solution. At 30% (v/v) and 20 %(v/v) honey concentrations, the self-healing coating with the highest charge transfer resistance stirred at 800 rpm and 1100 rpm, respectively, is due to slight aggregation and segregation of the honey-containing protective layer on the coated surface. Therefore, integrating PUF-encapsulated linseed oil with honey extract into the epoxy coating increased the corrosion resistance rate of Mg metal alloys. Considering the potential of this self-healing coating, it is conceivable to use it in industry to reduce the corrosion process and impact.